The impact of intergenerational support on the mental health of older adults: a discussion of three dimensions of support - Kang Ren; Jing Lan; Lingyu Ge; Lei Zhou (Frontiers in Public Health)
IntroductionThis paper examines the effects of intergenerational support on the mental health of older adults and elucidates the mechanisms underlying these effects.MethodsUtilizing data from the 2020 China Health and Retirement Longitudinal Study (CHARLS), We examine the effects of different dimensions of intergenerational support on the positive and negative emotions of older adults based on the main effect model and the buffer model. Then we employ instrumental variable methods to address key endogeneity concerns. The indirect effect mechanism through which children’s economic support influences the mental health of the older adults was examined using a mediation model. In addition, robustness tests and heterogeneity analyses were conducted.ResultsThe intergenerational support from children has a significant impact on the mental health of older adults. All three types of support contribute to the positive emotions of older adults. In terms of the impact on negative emotions, the regression coefficients for financial support and emotional support are significantly negative, while the direction of the effect of caregiving support is positive. Additionally, financial support promotes the mental health of the older adults by influencing their social participation. Heterogeneity analysis further indicates that the impact of intergenerational support varies across different subpopulations, with rural older adults particularly benefiting from emotional support.DiscussionOur findings reveal that financial support from adult children enhances older adults’ mental health by improving positive emotions and reducing negative emotions, and emotional support from children has a similar effect. However, while caregiving by adult children significantly boosts positive emotions among older adults, long-term caregiving also engenders feelings of guilt, which in turn exacerbates negative emotions and diminishes overall mental health. Our study emphasizes the need to consider Filial Piety Culture, social care support and social participation in order to improve older adults’ mental health.